MicroRNA signature in patients with hepatocellular carcinoma associated with type 2 diabetes - Elemeery, Moustafa Nouh; Mohamed, Marwa Anwar; Madkour, Marwa Ahmed; Shamseya, Mohammed Mohammed; Issa, Noha Mahmoud; Badr, Ahmed Noah; Ghareeb, Doaa Ahmed; Pan, Cheol-Ho (BAISHIDENG PUBLISHING GROUP INC, 2019)
BACKGROUND Nonalcoholic steatohepatitis-related cirrhosis is one of the liver complications in type 2 diabetes mellitus (T2DM) and reported to be a risk factor for developing hepatocellular carcinoma (HCC). A reliable screening biomarker of liver cirrhosis (LC) and HCC among T2DM patients is important to reduce the morbidity and mortality of this disease. MicroRNA (miRNA) is considered a key player in HCC and T2DM, and it might be a hidden culprit in diabetes-associated HCC, making it a promising reliable prognostic tool. AIM To investigate the signature of serum miRNAs as early biomarkers for the screening of HCC among diabetic patients. METHODS Expression profiles of miRNAs in serum samples of diabetic LC and diabetic HCC patients were assessed using Illumina sequencing; then, RT-qPCR was used to validate significantly altered miRNAs between the two groups. Candidate miRNAs were tested in serum samples of 200 T2DM patients, 270 LC patients, 200 HCC patients, and 225 healthy control subjects. Additionally, receiver operating characteristic (ROC) analysis, with area under the curve (AUC), was performed to assess the diagnostic performance of the screened miRNAs for discriminating HCC from LC and nonmalignant patients (LC + T2DM). RESULTS Expression of the sequenced miRNAs in serum was different in HCC vs LC-positive T2DM patients. Two miRNAs (miR-34a, miR-221) were significantly up-regulated and five miRNAs (miR-16, miR-23-3p, miR-122-5p, miR-198, miR-199a3p) were significantly down-regulated in HCC compared to LC patients. Analysis of ROC curve demonstrated that the combination of these seven miRNAs can be used as a reliable biomarker for detection of HCC in diabetic patients, as it could identify HCC with high diagnostic accuracy in diabetic LC patients (AUC = 0.993) and in diabetic nonmalignant patients (AUC = 0.961). CONCLUSION This study validates a panel of serum miRNAs that can be used as a reliable noninvasive screening biomarker of HCC among T2DM cirrhotic and noncirrhotic patients. The study recommends further research to shed light on a possible role of c-Met in T2DM-associated HCC via the miRNA regulatory pathway.
Keywords: CIRCULATING MICRORNAS; BIOMARKERS; EXPRESSION; DIAGNOSIS; CANCER; RISK; PROLIFERATION; METASTASIS; MIRNAS; SERUM